Using Self-Guided Treatment Software (ePST) to Teach Clinicians How to Deliver Problem-Solving Treatment for Depression. (14th November 2012) - Cartreine, James A.; Chang, Trina E.; Seville, Janette L.; Sandoval, Luis; Moore, John B.; Xu, Shuai; Hegel, Mark T.
Abstract : Problem-solving treatment (PST) offers a promising approach to the depression care; however, few PST training opportunities exist. A computer-guided, interactive media program has been developed to deliver PST electronically ( ePST ), directly to patients. The program is a six-session, weekly intervention modeled on an evidence-based PST protocol. Users are guided through each session by a clinician who is presented via hundreds of branching audio and video clips. Because expert clinician behaviors are modeled in the program, not only does the ePST program have the potential to deliver PST to patients but it may also serve as a training tool to teach clinicians how to deliver PST. Thirteen social workers and trainees used ePST self-instructionally and subsequently attended a day-long workshop on PST. Participants' PST knowledge level increased significantly from baseline to post- ePST (P = .001 ) and did not increase significantly further after attending the subsequent workshop. Additionally, attending the workshop did not significantly increase the participants' skill at performing PST beyond the use of the ePST program. Using the ePST program appears to train novices to a sufficient level of competence to begin practicing PST under supervision. This self-instructional training method could enable PST for depression to be widely disseminated, although follow-up supervision is still required.